2020
DOI: 10.3390/ijms21239174
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Differential Proteomic Analyses of Imitation Drought Stress Response in Sorghum bicolor Root at the Seedling Stage

Abstract: Drought is one of the most important constraints on the growth and productivity of many crops, including sorghum. However, as a primary sensing organ, the plant root response to drought has not been well documented at the proteomic level. In the present study, we compared physiological alteration and differential accumulation of proteins in the roots of sorghum (Sorghum bicolor) inbred line BT×623 response to Polyethylene Glycol (PEG)-induced drought stress at the seedling stage. Drought stress (up to 24 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 89 publications
2
30
0
Order By: Relevance
“…In this section, we summarize proteomic studies of sorghum plants under drought stress. Compared to the sorghum whole-plant transcriptomic analyses discussed above, the complementary proteomic work of this crop is extremely limited to a few publications [ 71 , 115 , 116 , 117 ] ( Table 3 ). This highlights the need for more studies to analyze the dynamics of sorghum proteomes in response to water deprivation as we seek to understand the molecular networks that contribute to the crop’s natural resilience to drought.…”
Section: Sorghum Proteomics Studies In Response To Drought Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we summarize proteomic studies of sorghum plants under drought stress. Compared to the sorghum whole-plant transcriptomic analyses discussed above, the complementary proteomic work of this crop is extremely limited to a few publications [ 71 , 115 , 116 , 117 ] ( Table 3 ). This highlights the need for more studies to analyze the dynamics of sorghum proteomes in response to water deprivation as we seek to understand the molecular networks that contribute to the crop’s natural resilience to drought.…”
Section: Sorghum Proteomics Studies In Response To Drought Stressmentioning
confidence: 99%
“…Another recent study [ 116 ] also analyzed the root proteome changes of the Bx623 sorghum inbred line in response to a 24 h treatment in 10% PEG-induced osmotic stress using 2D gel electrophoresis and matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry (MALDI-TOF-TOF MS) analysis. The study reported 105 differentially accumulated proteins in response to the PEG treatment, with 65 of these with a 2-fold change in abundance.…”
Section: Sorghum Proteomics Studies In Response To Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics has been developed as an important approach for studying plant functional genomics [ 1 ], which can be used to detect the post-transcriptional modification [ 2 ]. Two-dimensional gel electrophoresis (2-DE) was an efficient and powerful strategy to study complex gene expression at the protein level [ 3 5 ]. The quality of protein sample was the most crucial steps for optimal results in proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To study the proteome we used two-dimensional electrophoresis in combination with liquid chromatography-mass spectrometry (nanoLC-MS/MS) and peptide mass fingerprinting (PMF). Although there have been advances in the methodology of proteome research in recent years, the methods used in our study are still adequate and widely used in studies similar to ours [ 22 , 23 , 24 , 25 ]. We identified proteins showing differences in abundance in response to heat in the two buckwheat accessions.…”
Section: Introductionmentioning
confidence: 99%